Birokrasi Sipil dan Militer: Dominasi Aktor Militer Dalam Tubuh Kementerian Pertahanan Republik Indonesia - Andela Anggleni (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The writing of this article aims to find out the form of the military bureaucracy in Indonesia, especially in the Ministry of Defense (Kemenhan). And in the process of compiling it, it was inspired by a journal by Yusa Djuyandi and Muhammad Gufran Ghazian which highlighted the many retirees or even those still working in the military area who were included in the structure of state institutions, and the object of this research was the Ministry of Defense. However, in discussing this article, it takes sub-material regarding the form of order in the Ministry of Defense and the military bureaucracy in Indonesia. The data collection technique was carried out by means of a literature study by collecting translation documents from various forms such as journals, e-books, websites which have been compared so as to find the resulting data that can be used for the preparation of this article. The findings in this article, although in the leadership structure at the ministry of defense there are alumni from the military, their absence indicates that the environment created within the ministry of defense is rigid and hard like that of the military. The structure of the Kemenhan body has a form that has been determined according to a decision by the government in office at that time and can change according to the rules set. For now the function of the ministry of defense is as a coordinator in the area of national defense who is directly responsible to the president, providing and stipulating everything and the needs of the Indonesian armed forces in maintaining national defense.